Recommendations for community pharmacy to improve access to medication advice for people from ethnic minority communities: A qualitative person‐centred codesign study - Anna Robinson; Nicola O'Brien; Laura Sile; Harpreet K. Guraya; Thorrun Govind; Vicki Harris; Guy Pilkington; Adam Todd; Andy Husband (Wiley, 2022)
Abstract Introduction Medicines‐centred consultations are vital to support medicine effectiveness and optimize health outcomes for patients. However, inequalities negatively impact ethnic minority populations when accessing medicines advice. It is important to identify opportunities to improve access for these communities however, knowledge of how best to achieve this is lacking; this study will generate recommendations to improve access to medicines advice from community pharmacies for people from ethnic minority communities. Methods A series of codesign workshops, with four groups of patient‐stakeholders, were conducted between September-November 2021; they took place in‐person or via video call (adhering to COVID‐19 restrictions). Existing evidence‐based perceptions affecting access to medicines advice were critiqued and recommendations were generated, by use of reflexive thematic analysis, to improve access for ethnic minority patients. The workshops were audio‐recorded and transcribed verbatim. QSR NVivo (Version 12) facilitated data analysis. Results Twelve participants were recruited using purposive sampling; including eight UK citizens, two asylum seekers and two participants in receipt of residency visas. In total, four different ethnic minority groups were represented. Each participant took part in a first and second workshop to share and cocreate recommendations to improve access to medicines advice in community pharmacies. Three recommendations were developed and centred on: (i) delivering and providing culturally competent medicines advice; (ii) building awareness of accessing medicines advice from community pharmacies; and (iii) enabling better discussions with patients from ethnic minority communities. Conclusions These recommendations have the potential to support community pharmacy services to overcome ethnic inequalities affecting medicines advice; service commissioners should consider these findings to best meet the needs of ethnic minority patients. Cultural competence training for community pharmacy staff could support the creation of pharmacies as inclusive healthcare settings. Collaborative working with ethnic minority communities could enable specific tailoring of medicines‐centred services to best meet their needs. Patient or Public Contribution The National Institute for Health Research (NIHR) and Newcastle University Patient and Public Involvement and Engagement group had extensive input in the study design and conceptualization. Seven patient champions were appointed to the steering group to ensure that the research was conducted, and findings were reported, with cultural competence. Trial Registration Not applicable.